A Systematic Strategy for Discovering a Therapeutic Drug for Alzheimer’s Disease and Its Target Molecule - Yang, Zhiyou; Kuboyama, Tomoharu; Tohda, Chihiro (Frontiers in Pharmacology, 2017)
Natural medicines are attractive sources of leading compounds that can be used as interventions for neurodegenerative disorders. The complexity of their chemical components and undetermined bio-metabolism have greatly hindered both the use of natural medicines and the identification of their active constituents. Here, we report a systematic strategy for evaluating the bioactive candidates in natural medicines used for Alzheimer’s disease (AD). We found that Drynaria Rhizome (DR) could enhance memory function and ameliorate AD pathologies in 5XFAD mice. Biochemical analysis led to the identification of the bio-effective metabolites that are transferred to the brain, namely, naringenin and its glucuronides. To explore the mechanism of action, we combined the drug affinity responsive target stability (DARTS) with immunoprecipitation-liquid chromatography/mass spectrometry (LC/MS) analysis, identifying the collapsin response mediator protein 2 (CRMP2) protein as a target of naringenin. Our study indicates that biochemical analysis coupled with pharmacological methods can be used in the search for new targets for AD intervention.